Intermediate Heat Treatment - A New Proceeding for Aluminium Alloys Using Forming Limit Diagrams - Siefert, Kathleen; Merklein, Marion; Töpperwien, Almut; Nester, Winfried; Gruenbaum, Martin (Key Engineering 473, 2011)
This paper presents a new procedure for a heat treatment embedded between two cold forming steps. A first cold forming step induces a defined strain hardening in the material. The following step is the heat treatment which takes place in a furnace at various temperatures and for certain durations. The application of such an intermediate heat treatment reduces the strain hardening of the material and enhances the elongation. This allows a higher degree of deformation in the second cold forming operation. The achievable properties of the aluminum alloy AlMg4.5Mn (AA5182) were discussed in detail. Further investigations using Nakajima test setup revealed an increased formability of the material. First the Nakajima samples were pre-strained along different linear strain paths to a predefined strain value. Afterwards the samples were heat treated without allowing the aluminum alloy to recrystallize. After cooling down the samples to room temperature, the tests are continued until the material's fracture. As a result heat treatment dependent forming limit curves (FLC) are obtained. In comparison with a measured FLC at room temperature the support of the intermediate heat treatment on enhanced formability were shown. Furthermore the method is not restricted to AA5182 aluminum alloys. © (2011) Trans Tech Publications.
LFT Import::2019-08-05 (1745)
Keywords: Aluminum alloys; Aluminum sheet forming; Forming limit diagram; Heat treatment